Histo-Molecular Profile of Breast Cancer in Young Women in Togo - Toukilnan Djiwa; Baumaney Koui; Panakinao Simgban; Bagassam Mézéwè Sama; Mayi Bombonne; Brahima Doukouré; Tchin Darré (SAGE Publishing, 2022)
Introduction: The frequency of breast cancer in young women, corresponding to women under 40 years of age; varies from 5% to 7% in developed countries. The objective of this study was to contribute to the improvement of the management of breast cancer in young women in Togo, by establishing the molecular classification of these cancers. Methodology: This was a retrospective descriptive and analytical study from January 2010 to December 2020. Results: About 35 cases of breast cancer were identified in women under 40 years of age. The average age was 35.4 ± 3.5 years. The right breast was affected in 18 cases (51.43%). Histologically, 30 cases (85.72%) were invasive carcinoma of no special type (NST), 2 cases (5.71%) were invasive lobular carcinoma and micro-papillary carcinoma respectively, and 1 case (2.86%) was tubular carcinoma. There were 6 cases (17.1%) of grade I, 25 cases (71.4%) of grade II, and 4 cases (11.4%) of grade III. Molecularly, there were 20 cases (57.1%) of triple-negative subtype, 6 cases (17.1%) of Luminal B subtype, 05 cases (14.3%) of HER2-enriched subtype and 4 cases (11.4%) of Luminal A subtype. Conclusion: Breast cancers of young Togolese women express very weakly hormone receptors, with a predominance of a triple negative subtype.